INDUCED MATURATION IN THE INDIAN SHORT-FINNED EEL ANGUILLA BICOLOR BICOLOR McCLBLLAND - Dorairaj, K; Kandasami, D; Soundararajan, R (Indian Journal of Fisheries, 2011)
After acdimaitisiag the eels Anguilla bicolor bicolor in sea water, various'hormones viz., Gonadairaiphon F. S. H„ Gonadotraphon L. H. and ChorionicGonadotropin (Profasd) and OcirpHpituiiitiairy extracts were administered to differentdosages through intramuscular injections. By mepeated hormone JnjeotiJans maturatiionw:b induced in both tihe sexes. flHr*i*tLallty one imaile eeil which was given 2000 IUof Goaadoliraphon L.H. through four injections, reached spawning oondiiitilon 144days after the first injection. Mter partial spawning, the eedl died on the same day.The gamadosomiaitic index was 6.47 and eye index increased by 14.38%. Each spermsitozoiid has a comma shaped body and a long ital. One female eel on which wasadministered 240 mg of camp pituitary extract and 19,000 IU of Chorionic gonadotropin(Profasd) 'hormone (ttorouglh 16 tojeotiians, attained1 'staiip-irOpe' condition98 days after the first injedctfan and yielded 185,6 g of eggs on stripping. Thegonadosoiraaitic index was 33.5 The total weight and eye index of the eel increasedby 2.9% and 24.1%, respectively. The Mumiber of stripped aggs was estimated to be0.35 million. The mature eggs were spherical and reJatdvely umlortn in suae measuring1.00 mm (+ 0.08 mm) in diameter. Attempts made for amtificJJ fentdlisatonwene not successful. Fully developed ovary of A. bicolor bicolor is described1.